Double-layer shell ZnO voltage-sensitive ceramic material for improving Bi distribution on ZnO surface and preparation method of double-layer shell ZnO voltage-sensitive ceramic material

By preparing a continuously enclosed SiO2 modified layer on the outer layer of ZnO@Bi2O3 core-shell structure, the problem of Bi2O3 volatility in ZnO voltage-sensitive ceramics is solved, and the electrical performance and production efficiency of the ceramics are improved.

CN119774998APending Publication Date: 2025-04-08HUAZHONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411981677.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

During the high-temperature sintering of ZnO pressure-sensitive ceramics, Bi2O3 is prone to volatilization, resulting in poor electrical performance, and the prior art is difficult to effectively solve this problem.

Method used

A continuously enclosed silica modification layer was prepared by a liquid phase method on the outer layer of the zinc oxide core-shell particles coated with bismuth trioxide to prevent the volatility of Bi.

Benefits of technology

Effectively prevent the volatility of Bi2O3 during sintering, improve the electrical performance of ZnO pressure-sensitive ceramics, and reduce production costs and improve production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774998A_ABST
    Figure CN119774998A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of ZnO voltage-sensitive ceramics, and discloses a double-shell ZnO voltage-sensitive ceramic material for improving Bi distribution on the surface of ZnO and a preparation method of the double-shell ZnO voltage-sensitive ceramic material. According to the method, a continuously closed silicon dioxide modification layer is prepared on the outer layer of a bismuth trioxide coated zinc oxide core-shell particle through a liquid phase method, and the double-shell ZnO voltage-sensitive ceramic particle is obtained; and the ZnO voltage-sensitive ceramic is prepared by sintering the prepared double-layer shell ZnO voltage-sensitive ceramic powder as a raw material. Therefore, a continuous closed modification layer is prepared outside the ZnO-coated Bi2O3 core shell through the method, the problem that Bi2O3 volatilizes to the environment due to high-temperature sintering in the preparation process of the voltage-sensitive ceramic is solved, and the electrical property of the obtained voltage-sensitive ceramic is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of ZnO varistor ceramics, and more specifically, relates to a double-shell ZnO varistor ceramic material for improving Bi distribution on the ZnO surface and a preparation method thereof. Background Art

[0002] In the current research on the preparation of ZnO varistor ceramics, it is a common method to use micro- and nano-scale ZnO-based coated / doped powders and sinter them at high temperature. In this process, Bi2O3 is an indispensable additive as a "grain boundary skeleton". Since its melting point is lower than the sintering temperature of the ceramic, it will melt and transform into a liquid state during the sintering process and be distributed in the grain boundaries. Other additive elements are segregated at the grain boundaries and dissolved in the liquid phase to form grain boundary barriers. Improving the uniformity of Bi2O3 distribution at the grain boundaries can improve the electrical properties of ZnO varistor ceramics. Therefore, the researchers considered coating and modifying the micro- and nano-scale ZnO raw material powders. Specifically, Bi2O3 is coated on the surface of the ZnO raw material powder to form a micro- and nano-scale ZnO@Bi2O3 core-shell structure powder, and then sintering it.

[0003] The traditional preparation process is to add Bi2O3 and other additives to ZnO powder for mechanical mixing. The disadvantage of this method is that it is difficult to mix the powder evenly, resulting in uneven distribution of Bi elements, affecting the formation of grain boundary barriers, and resulting in poor overall electrical properties. The chemical precipitation method is used to wrap Bi2O3 on the outside of ZnO, which can greatly improve the distribution of Bi and enhance uniformity. However, due to the low melting point of Bi2O3, it will volatilize during high-temperature sintering and long-term heat preservation, resulting in Bi loss, which will also greatly affect the formation of grain boundary barriers. Therefore, the powder with ZnO@Bi2O3 structure can only solve the problem of poor Bi distribution uniformity, but cannot solve the problem of Bi volatilization.

[0004] In order to suppress or reduce the volatilization of Bi2O3, the method commonly used in industrial manufacturing is to add a gasket containing Bi2O3 to the sintered crucible and cover it to ensure the sealing of the sintered crucible. However, this method requires regular replacement of the gasket and the strict sealing of the sintered crucible. In addition, due to the number and spacing of the loaded pieces, this method easily leads to a large dispersion of product performance.

[0005] Therefore, exploring more suitable methods to inhibit the volatilization of Bi2O3 during high-temperature sintering has important engineering application value for the preparation and development of high-performance varistor ceramics. This can not only improve the performance stability of the product, but also reduce production costs and improve production efficiency. Summary of the invention

[0006] In view of the above defects or improvement needs of the prior art, the present invention provides a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface and a preparation method thereof, the purpose of which is to prepare a continuous closed silicon dioxide modification layer on the outer layer of bismuth trioxide-coated zinc oxide core-shell particles by a liquid phase method, thereby preventing the volatilization of Bi during the subsequent ceramic pressed tablet sintering process, thereby solving the technical problem that Bi2O3 evaporates to the environment during high-temperature sintering of the varistor ceramic and affects the electrical properties of the ZnO varistor ceramic.

[0007] In order to achieve the above-mentioned purpose, in the first aspect of the present invention, a method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface is provided, the method comprising preparing a continuous closed silicon dioxide modification layer on the outer layer of bismuth trioxide-coated zinc oxide core-shell particles by a liquid phase method to obtain double-shell ZnO varistor ceramic particles; wherein the liquid phase method is a hot water method, a sol-gel method or a non-uniform nucleation method.

[0008] As a preferred embodiment of the present invention, the liquid phase method is a sol-gel method, comprising:

[0009] After mixing bismuth trioxide-coated zinc oxide core-shell particle powder, a coupling agent and a solvent to form a suspension, the pH of the suspension is adjusted to 9-11, and a silicon source is added to fully react to obtain a double-shell ZnO varistor ceramic particle powder.

[0010] As a preferred embodiment of the present invention, the molar ratio of zinc oxide in the bismuth trioxide-coated zinc oxide core-shell particle powder to the silicon source is 1:(0.3-0.5).

[0011] As a preferred embodiment of the present invention, it is characterized in that the silicon source includes tetraethyl silicate, Na2SiO3 or SiCl4.

[0012] As a preferred embodiment of the present invention, the coupling agent includes 3-aminopropyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane.

[0013] As a preferred embodiment of the present invention, the reaction is: reacting at 25-30°C for 5-6h.

[0014] As a preferred embodiment of the present invention, the bismuth trioxide-coated zinc oxide core-shell particle powder is prepared by a chemical precipitation method, or by a combination of a chemical precipitation method and a hydrothermal method.

[0015] As a preferred embodiment of the present invention, the bismuth trioxide-coated zinc oxide core-shell particle powder is obtained by combining a chemical precipitation method with a hydrothermal method, specifically, a bismuth nitrate solution is mixed with nano zinc oxide, the pH of the mixed system is adjusted to 5-8 to form a suspension, and after washing, the bismuth compound is oxidized by a hydrothermal method and calcined to obtain the powder.

[0016] In the second aspect of the present invention, a double-shell ZnO varistor ceramic particle powder is prepared based on the preparation method of the first aspect of the present invention.

[0017] In the third aspect of the present invention, a ZnO varistor ceramic is provided, which is obtained by sintering the double-shell ZnO varistor ceramic particle powder as claimed in claim 8 as a raw material; wherein the sintering is: a heating rate of 2-5°C / min, a sintering temperature of 1000-1200°C, and a holding time of 0.5-4h

[0018] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0019] The present invention analyzes the distribution state of Bi2O3 in micro- and nano-scale ZnO@Bi2O3 core-shell structure powders, and finds that Bi2O3 is uniformly distributed on the ZnO surface in the form of fine particles, but Bi2O3 is exposed to the environment. This is the same as the Bi element in the traditional doped mixed powder, and there is a problem of easy volatility during the sintering process. Therefore, the present invention aims to modify a continuous closed shell layer on the outer layer of the ZnO@Bi2O3 core-shell particles through a liquid phase method, thereby preventing the volatilization of Bi in the subsequent ceramic powder sintering process, improving the problem of Bi2O3 volatilization to the environment caused by high-temperature sintering, and then improving the electrical properties of the resulting varistor ceramics.

[0020] In the preferred embodiment of the present invention, the sol-gel method has low preparation temperature, wide application, simple process, low cost, dense coating layer and adjustable thickness, and while protecting the micro- and nano-scale ZnO@Bi2O3 core-shell structure as much as possible, it can optimize the reaction system and product performance by adjusting process parameters.

[0021] Therefore, considering that the chemical precipitation method is used in the preparation of micro- and nano-scale ZnO@Bi2O3 core-shell structure powders, the driving force for shell formation is the van der Waals force, and the small driving force leads to a loose shell, while the modified layer requires a continuous and complete morphology, the liquid phase method is selected to prepare the modified layer on the surface of the ZnO@Bi2O3 core-shell structure. Furthermore, when selecting the outer layer modification material in combination with the liquid phase method, it is necessary to consider whether it is compatible with the preparation of the liquid phase method, and whether the obtained ZnO-based varistor ceramic powder can be used in subsequent use. Specifically, the powder surface modification material is selected from the doped oxides in the preparation of conventional ZnO-based varistor ceramics, and the selection range is determined to be MnO2, Co2O3, Cr2O3, Sb2O3, SiO2, and Al2O3, so as not to affect the performance of the final sintered product as much as possible; according to the characteristics of having a high melting point and inactive chemical properties during high-temperature sintering, that is, no melting or decomposition by itself, the selection range of the surface modifier is further narrowed to Cr2O3, SiO2, and Al2O3, so as to be able to withstand high temperature conditions (1000°C to 1200°C) The surface modification layer material of the powder can play the role of a shell well; if Cr2O3 is introduced, nitric acid needs to be added as a solvent, further narrowing the selection range of surface modification materials to SiO2 and Al2O3, so as to avoid dissolving Bi2O3 in the acidic environment during the preparation process, so as to minimize the damage to the original ZnO@Bi2O3 core-shell structure; finally, the preferred surface modification material is SiO2, because compared with Al2O3, SiO2 accounts for a larger proportion of the components of ZnO-based varistor ceramics, which is convenient for the subsequent preparation of varistor ceramic products. Adjustment of composition or performance.

[0022] Based on the above analysis, the advantages of the preparation scheme of the present invention are: (1) a continuous, complete and closed modification layer can be formed by the liquid phase method, which can wrap the Bi element in the shell, thereby preventing the Bi element from directly contacting the environment during the sintering process and reducing its volatilization to the external environment; (2) the SiO2 modification layer is selected to match the component materials used in the preparation of conventional ZnO-based varistor ceramics, that is, no new elements are introduced, thereby avoiding the impact on the performance of ZnO-based varistor ceramics; secondly, it matches the requirements of the liquid phase preparation method and the temperature requirements of subsequent high-temperature sintering; thirdly, more preferably, the SiO2 in the SiO2 modification layer will react with ZnO to form a spinel phase to further inhibit the growth of grains, which is beneficial to reducing the grain size after sintering and improving the overall microscopic uniformity of the varistor ceramic, thereby being able to simultaneously avoid the volatilization of the Bi element and promote the formation of the SiO2 modification layer. The reduction in particle size has the effect of jointly improving the electrical properties of varistors; (3) the surface modification layer can effectively prevent Bi2O3 from volatilizing to the environment during the sintering process, reducing the loss of Bi2O3, that is, the Bi2O3 content can be more accurately controlled during the powder preparation process; the electrical properties of the varistors obtained by sintering the surface-modified micro- and nano-scale ZnO@Bi2O3 core-shell structure powders (including micro- and nano-scale powders doped with other oxides) are improved by controlling the sintering temperature, heating rate, holding time and other parameters, and finally high-performance ZnO varistors and related products are obtained; (4) in the process of preparing the SiO2 micro-modification layer on the micro- and nano-scale ZnO@Bi2O3 core-shell structure powders by the sol-gel method, the thickness of the modification layer is quantitatively controlled by controlling the content ratio of ZnO, Bi2O3 and SiO2, thereby obtaining a surface modification layer with superior performance.

[0023] In summary, the present invention is based on low-cost raw materials, simple surface modification methods and flexible control methods. By modifying the surface of micro- and nano-scale ZnO@Bi2O3 core-shell structure powders before high-temperature sintering, the problem of Bi2O3 volatilization to the environment caused by high-temperature sintering is improved; and by adjusting relevant parameters of the sintering process, the electrical properties and stability of the varistor ceramics obtained by sintering the ZnO@Bi2O3 core-shell structure powders are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a microscopic morphology of particles of the double-shell ZnO varistor ceramic powder prepared in Example 1 of the present invention under a transmission electron microscope.

[0025] Figure 2 The distribution diagram of the elements of the double-shell ZnO varistor ceramic powder prepared in Example 1 of the present invention under a transmission electron microscope; Figure 2(a) is the superimposed distribution diagram of Zn and Bi elements, (b) is the distribution diagram of Bi element, (c) is the superimposed distribution diagram of Si and Zn elements, and (d) is the superimposed distribution diagram of Si, Zn, and Bi elements.

[0026] Figure 3 The microscopic morphology and element distribution diagram of the double-shell ZnO varistor ceramic prepared in Example 1 of the present invention under a scanning electron microscope; wherein Figure 3 (a) is a microscopic morphology diagram, (b), (c), (d) and (e) are the distribution diagrams of O, Si, Zn and Bi elements respectively.

[0027] Figure 4 The microscopic morphology and element distribution diagram of the ZnO varistor ceramic prepared in Comparative Example 2 of the present invention under a scanning electron microscope; wherein Figure 4 (a) is a microscopic morphology diagram, (b), (c), (d) and (e) are the distribution diagrams of O, Si, Zn and Bi elements respectively.

[0028] Figure 5 The microscopic morphology and element distribution diagram of the ZnO varistor ceramic prepared in Comparative Example 1 of the present invention under a scanning electron microscope; wherein Figure 5 (a) is a microscopic morphology diagram, (b), (c), (d) and (e) are the distribution diagrams of O, Si, Zn and Bi elements respectively. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] Unless otherwise specified, the raw materials or reagents used in the present invention are commercially available. All reagents are of commercial grade and used according to the received standards. The scientific and technical terms and abbreviations used in the present invention have the meanings commonly understood by those skilled in the art. Specifically, the ZnO@Bi2O3 used in the present invention is represented by Bi2O3 coated ZnO, and @ represents coating.

[0031] In the first aspect of the present invention, a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface is provided, the method comprising preparing a continuous closed silicon dioxide modification layer on the outer layer of bismuth trioxide-coated zinc oxide core-shell particles by a liquid phase method to obtain double-shell ZnO varistor ceramic particles; wherein the liquid phase method is a hot water method, a sol-gel method or a non-uniform nucleation method.

[0032] In the present invention, a method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface is preferably illustrated by a sol-gel method, comprising the following steps:

[0033] S1, preparing ZnO@Bi2O3 core-shell powder, at which point Bi2O3 is dispersed on the surface of ZnO;

[0034] S2. Based on the ZnO@Bi2O3 core-shell powder prepared in step S1 above, SiO2 is used to modify the surface of the ZnO@Bi2O3 core-shell powder by a sol-gel method to form a continuous closed oxide modification layer on the surface. The surface modification method is: ZnO@Bi2O3 core-shell powder, coupling agent and solvent are mixed to form a stable suspension; after adjusting the pH of the suspension to 9-11 and adding a silicon source for sufficient reaction, the precipitate is filtered out, washed, and dried to obtain a double-shell ZnO varistor ceramic powder.

[0035] In the present invention, the molar ratio of ZnO to silicon source in the ZnO@Bi2O3 core-shell powder can be selected to be 1:(0.3-0.5).

[0036] In the present invention, the optional silicon source includes organic silicon compounds such as tetraethyl silicate, Na2SiO3, or SiCl4, or strong alkaline metal silicates or silicon salts of strong acids.

[0037] In the present invention, the optional coupling agent includes amino- and glycidoxy-functionalized silane coupling agents such as 3-aminopropyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane.

[0038] In the present invention, the optional solvent is a mixed solvent of deionized water and ethanol, or anhydrous ethanol or methanol.

[0039] In the present invention, the pH of the suspension is adjusted by adding concentrated ammonia water or a dilute solution of a strong base, for example, by adding a NaOH solution to the system.

[0040] Preferably, the ZnO@Bi2O3 core-shell powder is prepared by a chemical precipitation method, or by a combination of a chemical precipitation method and a hydrothermal method.

[0041] Among them, an example is given of preparing bismuth oxide-coated zinc oxide powder by chemical precipitation and hydrothermal method (refer to patent 202310719063.1 applied for this topic)

[0042] The specific steps are as follows: (1) preparing solution A with bismuth nitrate, dispersing nano zinc oxide to prepare suspension B; adding solution A to suspension B for mixing, controlling the pH of the mixed solution to be 5-8, forming suspension C, washing to obtain bismuth compound-coated zinc oxide powder; (2) oxidizing the bismuth compound-coated zinc oxide powder obtained in step (1) by hydrothermal method, drying and collecting the product; (3) calcining the product in step (2) to obtain bismuth oxide-coated zinc oxide powder. The dosage parameters of the raw materials involved in the reaction, the process conditions, etc. are all referred to the specific disclosure of the patent.

[0043] In a second aspect of the present invention, a double-shell ZnO varistor ceramic powder prepared based on the above method is provided.

[0044] In the third aspect of the present invention, a double-layer ZnO varistor ceramic sheet is provided, which is made by spraying and granulating the double-layer ZnO varistor ceramic powder, pressing and molding after containing water, and sintering in a high-temperature box furnace.

[0045] The sintering conditions are as follows: a heating rate of 2-5°C / min, a sintering temperature of 1000-1200°C, and a holding time of 0.5-4h.

[0046] The above double-shell ZnO varistor ceramic sheet and its preparation method are further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and the scope of protection of the present invention is not limited thereto.

[0047] Embodiment 1:

[0048] Provided are a double-shell ZnO varistor ceramic powder and ceramic sheet for improving Bi distribution on the ZnO surface and a corresponding preparation method, which specifically includes the following steps:

[0049] 1. Preparation of ZnO@Bi2O3 single-layer core-shell structure powder, the specific steps are as follows:

[0050] (1) Weigh 5 g ZnO and 1.5 g bismuth nitrate pentahydrate (Bi / Zn molar ratio 5%) and add an appropriate amount of 1 mol / L NaOH solution.

[0051] (2) Add 300 ml of deionized water and 150 ml of ethanol to ZnO and disperse it using an ultrasonic disperser for 1-2 hours.

[0052] (3) Add 1.5 ml of concentrated HNO3 (65% by mass) to bismuth nitrate pentahydrate, dilute to 20 ml with deionized water, place on a magnetic stirrer and stir until dissolved to obtain a bismuth nitrate solution.

[0053] (4) The dispersed ZnO solution was placed on a magnetic stirrer (800 r / min), and bismuth nitrate solution and NaOH solution were added dropwise alternately to control the pH value in the range of 5-8.

[0054] (5) When the bismuth nitrate solution is added, use NaOH solution to control the pH value to about 8 to ensure complete precipitation. Let it stand for ten minutes, and white floccules will settle at the bottom. Pour off an appropriate amount of the supernatant and transfer the remaining part to a centrifuge.

[0055] (6) After washing four times with deionized water and alcohol alternately, the precipitate was transferred to a beaker, and then the pH was adjusted to 10.5 and transferred to a reactor. The reactor was placed in an oven and the hydrothermal reaction conditions were set to 120°C for 9 h.

[0056] (7) After the hydrothermal reaction, transfer the solution into a glass bowl and continue to place it in an oven for drying.

[0057] (8) The dried powder was ground, sieved and collected, transferred to a high temperature box furnace, heated to 415°C at 2°C / min and calcined for two hours to finally obtain ZnO@Bi2O3 powder. At this time, the coating structure is a particle-type coating structure, that is, Bi2O3 is dispersed on the ZnO surface.

[0058] 2. Preparation of double-shell ZnO varistor ceramic powder, i.e., preparation method in which SiO2 is coated on the outside of ZnO by sol-gel method, the specific steps are as follows:

[0059] (1) Weigh 0.5 g ZnO@Bi2O3 powder, add 50 ml deionized water, 200 ml ethanol and 5 ml coupling agent (3-aminopropyltriethoxysilane) and disperse by ultrasonic for 1 h to obtain a stable suspension.

[0060] (2) Dissolve 5 ml of concentrated aqueous ammonia in a mixed solution containing 10 ml of deionized water and 10 ml of ethanol, stir evenly and add to the stable suspension. Then, stir the mixed solution magnetically at room temperature for 0.5 h using a magnetic stirrer.

[0061] (3) 4 ml of tetraethyl silicate (Si / Zn molar ratio: 0.3) was added to the mixed solution, and the mixed solution was magnetically stirred at a constant temperature of 30° C. for 5 h.

[0062] (4) After sufficient reaction, the mixture was centrifuged using an ultracentrifuge, the precipitate was filtered, and then washed alternately with deionized water and ethanol for three times.

[0063] (5) Drying in a drying oven at 60 °C for 8 h to obtain SiO2-coated ZnO@Bi2O3 powder, i.e., double-shell ZnO varistor ceramic powder.

[0064] 3. Preparation of double-shell ZnO varistor ceramic sheet, the specific steps are as follows:

[0065] (1) The double-shell ZnO varistor ceramic powder prepared in step 2 is weighed to a mass of 0.49 g, and 20% by mass of PVA (polyvinyl alcohol, used as a binder to improve the strength of the formed body) is added to the powder for granulation.

[0066] (2) The granulated material is dried, ground, sieved, and hydrated, and then pressed into a green body with a diameter of 12 mm and a thickness of about 2 mm.

[0067] (3) After pre-sintering and debinding the green body, formal sintering is performed.

[0068] (4) The debinding green body is placed in a crucible without laying a pad containing Bi2O3 on the bottom, the lid is covered to ensure a good seal, and the green body is placed in a high-temperature box furnace and sintered at 1050°C for 0.5h to finally obtain a ZnO varistor ceramic sheet with a double-layer shell.

[0069] Comparative Example 1:

[0070] A preparation scheme for a ZnO varistor ceramic sheet is provided, and the preparation scheme is the same as that of Example 1, except that the crucible is not covered during sintering in the comparative example, that is, the sintering is performed in an open air environment.

[0071] Comparative Example 2:

[0072] A preparation method of a ZnO varistor ceramic sheet is provided, which mainly comprises directly adding SiO2 in the same molar ratio as in the embodiment to the ZnO@Bi2O3 core-shell powder to prepare a composite powder, and then sintering the composite powder at high temperature, and specifically comprises the following steps:

[0073] (1) Weigh 0.5 g of ZnO@Bi2O3 single-layer core-shell structure powder and 0.086 g of SiO2 powder (Si / Zn molar ratio is 0.3) respectively.

[0074] (2) Mix and grind the two powders in an agate mortar for 1 h to make them evenly mixed.

[0075] (3) The uniformly mixed powder obtained in step 2 is weighed to a mass of 0.56 g, and 20% by mass of PVA (polyvinyl alcohol, used as a binder to improve the strength of the formed body) is added to the powder for granulation.

[0076] The following steps and conditions are the same as those in Example 1, namely:

[0077] (4) The granulated material is dried, ground, sieved, and hydrated, and then pressed into a green body with a diameter of 12 mm and a thickness of about 2 mm.

[0078] (5) After the above green body is pre-sintered to remove binder (the conditions are the same as those in Example 1), formal sintering is performed.

[0079] (6) The debinding green body is placed in a crucible without laying a pad containing Bi2O3 on the bottom layer, the lid is covered to ensure a good seal, and the green body is placed in a high-temperature box furnace and sintered at 1050°C for 0.5h to finally obtain a ZnO varistor ceramic sheet with a double-layer shell.

[0080] Test standard: The ceramic powders and ceramic sheets prepared in the above examples and comparative examples were tested by transmission electron microscopy (TEM) morphology and element distribution (EDS spectrum), scanning electron microscopy (SEM) morphology and element distribution (EDS spectrum). The test conditions were vacuum conditions. The test results are as follows:

[0081] like Figure 1 This is a microscopic morphology of the grains of the double-shell ZnO varistor ceramic powder prepared in Example 1. It can be seen that there is a continuous and complete shell-like morphology on the surface of the grains.

[0082] like Figure 2 This is the element distribution test diagram of the double-shell ZnO varistor ceramic powder prepared in Example 1. It can be seen that the Si element is distributed in a continuous and complete surrounding shape around the Zn element.

[0083] like Figure 3 The microscopic morphology and element distribution of the double-shell ZnO varistor ceramic sheet prepared in Example 1. The Si and Bi elements are evenly distributed in the shown area, and the segregation of the Bi element at the grain boundary can be clearly seen. From the atomic percentage statistics of the elements, it can be seen that the Bi / Zn atomic ratio in the sintered ceramic is 0.024.

[0084] like Figure 4 The microscopic morphology and element surface distribution of the ZnO varistor ceramic sheet prepared in Example 2 show that the Si element is not evenly distributed in the shown area, while the Bi element is relatively evenly distributed. However, the Bi / Zn atomic ratio is calculated to be 0.0093, which shows that the loss of Bi element is greatly increased compared with the modified powder.

[0085] like Figure 5 The microscopic morphology and element distribution of the ZnO varistor ceramic sheet prepared in Example 1 show that the Si element is still evenly distributed in the region shown, and the segregation of the Bi element at the grain boundary is slightly uneven. However, by comparing the Bi / Zn atomic ratio, it is found that the value is Figure 3 The consensus value is 0.024.

[0086] contrast Figure 3 , Figure 4 , Figure 5From the test results, it can be clearly seen that the Bi / Zn atomic ratio of the surface-modified micro- and nano-scale ZnO@Bi2O3 core-shell powders is consistent when they are covered and fired under the same sintering system; after the unmodified powders are added with SiO2 of the same molar ratio to make composite powders and then covered and fired under the same sintering conditions, the Bi / Zn atomic ratio is greatly reduced, indicating that the modification layer involved in the present invention can significantly inhibit the loss caused by the volatilization of the Bi element during high-temperature sintering, and keep the Bi element content unchanged under both covered and open firing conditions, which can greatly reduce the stringent requirements on the sealing of the sintering crucible during the sintering process.

[0087] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of protection of the present invention and its equivalent technology, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the scope of protection of the present invention.

Claims

1. A method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface, characterized in that: The method is to prepare a continuous closed silicon dioxide modification layer on the outer layer of bismuth trioxide-coated zinc oxide core-shell particles by a liquid phase method to obtain double-shell ZnO varistor ceramic particles; wherein the liquid phase method is a hot water method, a sol-gel method or a non-uniform nucleation method.

2. The method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface according to claim 1, characterized in that: The liquid phase method is a sol-gel method, comprising: After mixing bismuth trioxide-coated zinc oxide core-shell particle powder, a coupling agent and a solvent to form a suspension, the pH of the suspension is adjusted to 9-11, and a silicon source is added to fully react to obtain a double-shell ZnO varistor ceramic particle powder.

3. The method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface as claimed in claim 2, wherein the molar ratio of zinc oxide in the bismuth trioxide-coated zinc oxide core-shell particle powder to the silicon source is 1:(0.3-0.5).

4. The method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface as claimed in claim 2, characterized in that: The silicon source includes tetraethyl silicate, Na2SiO3 or SiCl4.

5. The method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface as claimed in claim 2, characterized in that: The coupling agent includes 3-aminopropyltriethoxysilane or γ-methacryloxypropyltrimethoxysilane.

6. The method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface as claimed in claim 2, characterized in that: The reaction is carried out at 25-30°C for 5-6 hours.

7. The method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface as claimed in claim 2, characterized in that: The bismuth trioxide-coated zinc oxide core-shell particle powder is prepared by a chemical precipitation method, or by combining a chemical precipitation method with a hydrothermal method.

8. The method for preparing a double-shell ZnO varistor ceramic material with improved Bi distribution on the ZnO surface as claimed in claim 7, characterized in that: The bismuth trioxide-coated zinc oxide core-shell particle powder is prepared by combining a chemical precipitation method with a hydrothermal method, specifically, mixing a bismuth nitrate solution with nano zinc oxide, adjusting the pH of the mixed system to 5-8 to form a suspension, washing, oxidizing the bismuth compound by a hydrothermal method, and calcining to obtain the bismuth trioxide-coated zinc oxide core-shell particle powder.

9. Double-shell ZnO varistor ceramic particle powder obtained by the preparation method as described in any one of claims 1 to 8.

10. A ZnO varistor ceramic, characterized in that: It is obtained by sintering the double-shell ZnO varistor ceramic particle powder as claimed in claim 9 as raw material; wherein the sintering is: heating rate is 2-5°C / min, sintering temperature is 1000-1200°C, and insulation time is 0.5-4h.

Citation Information

Patent Citations

  • Bismuth oxide coated zinc oxide powder and preparation method and application thereof

    CN116835973B